The Effect of Transformational Leadership, Compensation, and Work Environment on Employee Loyalty(Case Study at PT Bank Syariah Indonesia Tbk South Bekasi Area) - Nissya Vadila; Anita Novialumi (Indonesia Economic Journal, 2026)
Employee loyalty is a key factor in maintaining the smooth operation of a company, particularly in the Islamic banking sector, which is currently facing competitive challenges and a digital transformation process. PT Bank Syariah Indonesia Tbk, Bekasi Selatan branch, recorded an increase in turnover rate of 6.72% during the 2024–2025 period, rising from 2.24% to 4.58%. This figure indicates a decline in employee satisfaction and the need for organized action to address it. This study aims to analyze the impact of transformational leadership, compensation systems, and work environment conditions on employee loyalty levels, both individually and simultaneously. A quantitative methode was used by collecting data through questionnaires. All 125 employees were used as respondents using the saturated sampling method. The instrument consists of 25 statement items using a Likert scale with five response levels. Data analysis was carried out by testing validity, reliability, classical assumptions, multiple linear regression, t-test, F-test, and the coefficient of determination (R²) using SPSS software version 27.0. The study shows that transformational leadership style has a positive and significant impact on employee loyalty levels with a coefficient value of 0.398. Compensation has a positive and significant impact (β = 0.444). In contrast, the work environment does not have a significant impact with a significance level of 0.174. Simultaneously, all three independent variables have a significant influence on employee loyalty levels. The Adjusted R-squared value of 0.479 indicates that 47.9% of the variation in employee loyalty levels can be explained by the three variables used, while the remainder is influenced by other factors outside the model.